Estudo comparativo de carragenanas comerciais Kappa, Iota e Lambda no processo inflamatório em ratos :edema intraplantar e pleurisia - Silva, Fernando Roberto Ferreira (2005)
The Iota, Kappa and Lambda commercial carrageenans are rarely pure and normally contain varying amounts of the other types of carrageenans. The exact amount of impurity depends on the seaweed source and extraction procedure. Then, different analysis methods have been applied for determination of the main constituents of carrageenans because these three carrageenans are extensively used in food, cosmetic and pharmaceutical industry. The electrophoresis of these compounds proved that the carrageenans are constituted by sulfated polysaccharides. These compounds were characterized by colorimetric methods and was observed that the Lambda carrageenan shown the greater value (33.38%) of sulfate. These polymers were examined by means of 13C NMR spectroscopy and infrared spectra. The polysaccharides consisted mainly of units alternating of sulfated galactoses and anhydrogalactoses. The aim of the study was also to test the inflammatory action of these different polysaccharides. A suitable model of inflammation is acute sterile inflammation of the rat hind limb induced by carrageenan. Paw edema was induced by injecting carrageenans (κ, ι and λ) in saline into the hind paw of a male Wistar rats (175–200 g). The pathway to acute inflammation by carrageenan (kappa, iota and lambda) were expressed as time-edema dependence and measured by paw edema volume. For this purpose, was used an apparatus (pakymeter), which makes it possible to measure the inflammation (swelling of the rat foot) with sufficient accuracy. The results showed that κ-carrageenan (1%) have an edema of 3.7 mm and the paw edema increase was time and dose dependent; the ι-carrageenan (0.2%) caused an edema of 4 mm and the λ-carrageenan (1%) caused an edema of 3.6 mm. Other model was used in this study based in the inflammation of pleura for comparatives studies. Injection of carrageenans into the pleural cavity of rat induced an acute inflammatory response characterized by fluid accumulation in the pleural cavity, a large number of neutrophils and raised NO production. The levels of NO were measured by Griess reactive. The ι-carrageenan caused the greater inflammation, because it has high concentration of nitrite/nitrate (63.478 nmoles/rat), exudato volume (1.52 ml) and PMNs (4902 x 103 cells). Quantitative evaluation of inflammations of rats is a useful and important parameter for the evaluation of the efficacy of anti-inflammatory drugs